Proceedings of the 18th International Conference on Evaluation and Assessment in Software Engineering 2014
DOI: 10.1145/2601248.2601274
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a community workshop to identify and rank barriers to the systematic literature review process

Abstract: Systematic Literature Reviews (SLRs) are an important tool used by software engineering researchers to summarize the state of knowledge about a particular topic. Currently, SLR authors must perform the difficult, time-consuming task in largely manual fashion. To identify barriers faced by SLR authors, we conducted an interactive community workshop prior to ESEM'13. Workshop participants generated a total of 100 ideas that, through group discussions, formed 37 composite barriers to the SLR process. Further anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Whilst this has generated feedback identifying possible implementation problems and proposed solutions, it has also aided the review of the initial guidelines proposed by Kitchenham [8,19,37,44,45]. One of the major problems faced by SR users is the amount of time and effort required to conduct a thorough SR [36,42].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this has generated feedback identifying possible implementation problems and proposed solutions, it has also aided the review of the initial guidelines proposed by Kitchenham [8,19,37,44,45]. One of the major problems faced by SR users is the amount of time and effort required to conduct a thorough SR [36,42].…”
Section: Introductionmentioning
confidence: 99%
“…The actual synthesis as such is difficult, but the key problem making it difficult is the primary studies. Two recent papers [5] and [6] present similar findings, Guzman et al [5] identified the primary studies and their quality as the main challenge with respect to synthesis, and Hassler et al [6] report that one of the main barriers for conducting systematic literature studies is the quality of the primary studies.…”
Section: Discussionmentioning
confidence: 67%
“…Hassler et al [6] report on a workshop where experienced researchers discuss some of the challenges with respect to systematic literature reviews. With respect to quality assessment, the highest ranked issues is the quality of the primary studies, which is also the second highest concern overall reported in Hassler et al…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…One way of addressing these difficulties is to have extensive SLR planning activities before the conducting phase. It is believed that adequate planning activities is likely to improve the overall performance of the SLR process [7]. Poor planning and inappropriate review strategy will affect the overall quality and efficiency of SLR process.…”
Section: Introductionmentioning
confidence: 99%